Pediatric genital warts successfully treated with photodynamic therapy - Federica Li Pomi; Andrea d'Aloja; Antonio Di Tano; Mario Vaccaro; Francesco Borgia (Dermatology Reports, 2024)
Genital warts (GWs) are the most common sexually transmitted infections worldwide, caused by the human papillomavirus (HPV). In adults, the primary mode of transmission is through sexual contact, whereas in children it can occur through skin-to-skin or skin-to-mucosa contact and be sexual or non-sexual. The increasing prevalence of GWs in children has renewed the interest in therapeutic management which still presents a unique challenge, being influenced by many variables including size, quantity, and location of warts, as well as the presence of comorbidities. Photodynamic therapy (PDT) has already shown encouraging results in treating viral warts in adult patients, but its use is still not standardized in the pediatric population. On this topic, we report the case of an otherwise healthy 5-year-old child affected by GWs, successfully treated with three sessions of PDT with 10% 5-aminolaevulinic acid (ALA), at one-month intervals. Our case is paradigmatic of the potentiality of PDT to treat difficult lesions in a pediatric setting.